2017
DOI: 10.1590/2179-8087.073914
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Espaçamento, Idade e Irrigação no Volume e Densidade Básica do Eucalipto

Abstract: RESUMO O objetivo do trabalho foi avaliar a influência da idade, irrigação e espaçamento no volume e densidade básica da madeira de eucalipto. Os materiais utilizados foram dois clones Eucalyptus grandis × Eucalyptus urophylla com idades de 6 e 12 meses provenientes de plantios em duas regiões, uma irrigada e outra região não irrigada, com espaçamentos de 3×0,5; 1,5×2, 3×1; 3×2 e 3×3 m. O volume foi determinado conforme o método de Smalian, sendo determinada também a densidade básica ponderada. Os maiores valo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
2
2
1
2
Order By: Relevance
“…According to Moulin et al (2017b), a high planting density results in greater competition for nutrients, water, and light, resulting in a lower basic density of the wood, corroborating the results found in this study. However, for energy purposes, a short cutting cycle and greater volume per area are essential for continuous production that meets local demand (SILVEIRA, REINER, SMANIOTTO, 2014).…”
Section: Resultssupporting
confidence: 91%
“…According to Moulin et al (2017b), a high planting density results in greater competition for nutrients, water, and light, resulting in a lower basic density of the wood, corroborating the results found in this study. However, for energy purposes, a short cutting cycle and greater volume per area are essential for continuous production that meets local demand (SILVEIRA, REINER, SMANIOTTO, 2014).…”
Section: Resultssupporting
confidence: 91%
“…Schwerz et al (2019) reported better growth efficiency for stands of Acacia mearnsii cultivated in southern Brazil using the denser spacing of 2.0 × 1.0 m compared to larger spacings of 2.0 × 1.5 m, 3.0 × 1.0 m and 3.0 × 1.5 m. The authors related the results to the greater amount of radiation intercepted by tree canopy in the denser spacings, which allows higher photosynthetic rate, and consequently greater radiation use efficiency for increasing forest biomass. Similar results were observed for different species and tree ages within the genera Eucalyptus (Berger et al 2002;Eufrade-Junior et al 2016;Moulin et al 2017) and Gmelina (Tenorio et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…However, although this statement and the growing spaces used in this study, equal to 2, 3 and 4.5 m², did not affect the property of static bending of Eucalyptus grandis wood, others researches concluded that larger plant spacing resulted in better technological properties [17] and, in the case of energy production by wood, larger plant spacing also became more attractive [18]. In general, the spacing has not shown influence on the wood mechanical properties may occur due to the fast rotation that is given to eucalyptus wood in pure stands, as occurred in the present study because it is a 7-year stand, because research has shown that in the first years the plant spacing does not change the characteristics that add quality to wood [8].…”
Section: Discussioncontrasting
confidence: 68%